NATO in the Trump era : an alliance of interests? - Selden, Zachary A. (Routledge, 2026)
This book argues that, even by the transactional metrics of the Trump administration, the transatlantic Alliance is of enduring value to both the US and Europe.Through interviews with a wide range of European Union and NATO staff, the book points to a clear shared interest in containing the influence of the People's Republic of China as well as its partnership with Russia. It also demonstrates that both Europe and the US will be under strain to maintain defense spending at current levels in the next decade, because ageing populations will demand increasingly larger portions of government spending that must be drawn from a shrinking working-age population. The book concludes by offering clear recommendations for how the Trump administration could achieve its stated goals through a renewed transatlantic relationship rather than an abandonment of Europe.This book will be of interest to students of transatlantic relations, foreign policy, security studies, and International Relations.
Keywords: Trump, Donald, -- 1946-; North Atlantic Treaty Organization.; Security, International.; Europe -- Military relations -- United States.; United States -- Military relations -- Europe.; elektronické knihy; electronic books